1987
DOI: 10.1055/s-0038-1645963
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Fibrinogen in the Aggregation of White Blood Cells

Abstract: SummaryIn order to verify whether leukocyte aggregation correlated with aggregation of other cellular elements during inflammation, we examined the state of leukocyte adhesiveness/aggregation (LAA) in the peripheral blood and red cell aggregation. Correlation was found to be significant as was the correlation between LA A and fibrinogen, and with the fibrin/fibrinogen degradation products concentration during various inflammatory states. In vitro leukocyte aggregation was decreased when the cells were suspende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…In fact, it can be induced by an in vivo infusion of immunoglobulins [22] and abolished by plasmapheresis [23]. This dependence on plasma factors have been shown also for the enhanced leukocyte adhesiveness/aggregation [21,24]. In addition, rheological studies have suggested that increased erythrocyte [25] or leukocyte [26] aggregability might have deleterious rheological consequences in term of tissue hypoperfusion and less efficient oxygenation [10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, it can be induced by an in vivo infusion of immunoglobulins [22] and abolished by plasmapheresis [23]. This dependence on plasma factors have been shown also for the enhanced leukocyte adhesiveness/aggregation [21,24]. In addition, rheological studies have suggested that increased erythrocyte [25] or leukocyte [26] aggregability might have deleterious rheological consequences in term of tissue hypoperfusion and less efficient oxygenation [10].…”
Section: Discussionmentioning
confidence: 96%
“…We have raised the possibility that this stimulation might have rheological consequences in terms of the appearance of adhesive erythrocytes and leukocytes in the peripheral blood. This assumption is based on the knowledge that the acute-phase response is accompanied by the synthesis of multiple adhesive proteins and that part of them might be involved in the induction and/or maintenance of enhanced red [8,9,20] or white [21] blood cells adhesiveness/aggregation in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Both membrane adhesive proteins on the surface of white blood cells [27,28] and plasmatic proteins [29,30] might participate in the induction and/or maintenance of increased LAA in the peripheral blood during inÂŁammation. The present study addresses both topics of the expression of adhesive proteins of white blood cells as well as the possibility that plasma proteins are involved as well.…”
Section: Discussionmentioning
confidence: 99%
“…Increased adhesiveness/aggregation of WBC can be attributed to both cellular [19] and plasmatic factors [20]. We addressed this issue by studying the presence of leukocyte adhesion molecules that participate in WBC adhesiveness, namely CD11b/CD18 and CD62L antigens.…”
Section: Discussionmentioning
confidence: 99%